Preliminary neutronic assessments for the development of the VIS/IR diagnostic systems located in the ITER EPP - Palermo, Iole; Mota, Fernando; Rios, Luis; Catalán, Juan Pablo; Alonso, Javier; Ibarra, Angel (ELSEVIER SCIENCE SA, 2015)
The paper focuses on the nuclear analyses of the ITER Equatorial Port Visible/Infrared Wide Angle Viewing System (VIS/IR WAVS). This instrument comprises of viewing systems in the 4 Equatorial Ports (EP) 3, 9, 12 and 17. The main mission of this diagnostic is to support the operation of the tokamak by providing visible and infrared viewing and temperature data of the first wall to protect it from damage. Its design is driven by both the tokamak severe environment and the high performances required for machine protection. New nuclear studies have been carried out for the development of the diagnostic and for test purposes under ITER-like irradiation conditions in order to choose the most appropriate materials for the optical components. Thus, three neutronic analyses have been carried out: the first in order to verify if silver could be used as a covering material for the optical components in different location of the Interspace area; the second in order to establish the irradiation time required in a Co-60 gamma facility (at CIEMAT) for testing purposes of the sapphire vacuum window; and the third to give more detailed specifications for the irradiation campaigns under gamma (in the Co-60 facility) and neutrons (at SCK•CEN BR2 reactor), about the time required to achieve the same dose than the one accumulated in ITER at the end-of-life (EOL) in the different components of the Port area for the materials proposed as substrate and coatings. The neutronic and activation calculations have been performed using the Monte Carlo code MCNP5, the activation code ACAB and the cross section libraries FENDL 2.1 and EAF-2007. The description of the simulations and their results are presented in this paper
Keywords: neutronics, ITER, diagnostics, optical materials